2020
DOI: 10.1111/jvim.15788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term overfeeding of a high‐energy diet on glucose tolerance in Shetland pony mares

Abstract: Background: Overfeeding is associated with obesity and insulin dysregulation (ID), which are both risk factors for equine metabolic syndrome. How chronic overfeeding affects development of these factors is poorly understood.Objectives: To examine the influence of long-term high-energy diet provision on body condition and ID.Animals: Eleven Shetland pony mares. Methods:In a 3-phase study, the high-energy group (n = 7) was fed 200% of net energy (NE) requirements (hay; concentrate: 36% sugar and starch, 13% fat)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
(78 reference statements)
2
13
0
Order By: Relevance
“…In cattle, exposing oocytes to insulin during in vitro maturation resulted in a decreased blastocyst formation rate and led to upregulation of genes involved in lipid metabolism in day 8 blastocysts, indicating that exposure of oocytes to insulin had an effect that lasted until at least the blastocyst stage [ 32 ]. Since the overfed mares in the present study were previously shown to exhibit hyperinsulinemia in response to an oral glucose challenge [ 16 ], it seems reasonable to propose that elevated plasma and FF insulin concentrations may have compromised oocyte and embryo developmental competence. However, follicular fluid insulin concentrations were not measured.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In cattle, exposing oocytes to insulin during in vitro maturation resulted in a decreased blastocyst formation rate and led to upregulation of genes involved in lipid metabolism in day 8 blastocysts, indicating that exposure of oocytes to insulin had an effect that lasted until at least the blastocyst stage [ 32 ]. Since the overfed mares in the present study were previously shown to exhibit hyperinsulinemia in response to an oral glucose challenge [ 16 ], it seems reasonable to propose that elevated plasma and FF insulin concentrations may have compromised oocyte and embryo developmental competence. However, follicular fluid insulin concentrations were not measured.…”
Section: Discussionmentioning
confidence: 92%
“…As reported in a previous article, the HE mares showed insulin dysregulation (ID) after 10–12 weeks of overfeeding in 2014, as determined by periodic oral glucose tolerance tests [ 16 ]. During the winter period when the HE diet was stopped, the ID was reversed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General health of all mares was assessed daily by monitoring heart rate, rectal temperature and gait. The ID status of the HE mares was examined via periodic oral glucose tolerance testing, which was performed 3 to 4 times per study year and reported in a previous study [ 24 ]. The experimental protocol was approved by the Committee on Animal Welfare of Utrecht University (DEC 2014.III.01.004).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to determine the effect of maternal overfeeding on early epigenetic reprogramming and pathways for conceptus nutrient uptake. Mares were fed either a high-energy (HE) diet equating to 200% of net energy requirements, which resulted in gradual onset of obesity and ID [ 24 ], or a control maintenance diet. The effect of maternal overfeeding on pre-implantation conceptus development was investigated by transferring day-seven embryos (i.e., immediately after blastocyst formation) between HE and control mares and assessing the expression of genes coding for various imprinted genes and DNMTs, glucose and amino acid transporters in the conceptus membranes at day 28 of gestation (i.e., late in the pre-implantation period).…”
Section: Introductionmentioning
confidence: 99%